Plans for the future: an examination of research methodology and education in parks and protected area visitor use management - Brunson, Michael (Kansas State University, 2021)
Identification, let alone an understanding, of assumptions in the visitor use management (VUM) field are poorly understood and addressed in the literature. While various assumptions – statements or assessments that are not necessarily rooted in factual evidence – that comprise certain outdoor recreation and VUM theoretical frameworks or methods are mentioned, there is a dearth of information on what those assumptions specifically entail and what implications they have. This dissertation offers three separate, yet interconnected, studies which help address this gap in knowledge of how prevalent VUM specific assumptions are and what their implications may be for VUM related research approaches, parks and protected area (PPA) management decisions, and educational influences of future PPA managers. To help address these ideas, this dissertation focuses on three main research questions: One, what research-related assumptions do VUM experts believe are present in the field? Two, how valid is a documented assumption related to the management of PPAs? And three, are any of the assumptions identified from the first research question being promulgated in undergraduate recreation-related classrooms? To address the first question, a Delphi study was conducted in which 8 VUM experts from around the United States (U.S.) generated a list of 28 research-related assumptions they believe to be present within the VUM field. These assumptions fell into four main categories: methodological, experiential, management-related, and natural resource-related. Through the Delphi process, assumptions were ranked by the expert panelists according to how prevalent, or pervasive, they believed them to be. Through an iterative process, 17 assumptions remained in which the top three from each category were identified. These 17 assumptions represented those that that the panelists agreed were the most pervasive in the VUM field. Specific identification of these assumptions contributes to the overall efficacy of VUM research approaches, as well as the overall management of PPAs around the U.S.. The second question addresses the PPA manager-visitor and how the preconceived notions and assumptions of managers may impact VUM-related management decisions. The application of VUM strategies and tools has been steadily developing as a discipline to meet the changing recreation needs and behaviors of visitors to many PPAs, yet it is important that these methods and approaches are appropriately evaluated to maintain their efficacy. Manager assumptions and preconceived notions can play into this efficacy. Using data from a previous visitor use study conducted at a U.S. national park, the role of manager assumptions and preconceived notions was investigated, particularly in relation to how PPA managers understand visitor norms, preferences, and needs. During this study, park managers were asked to respond to the same surveys their visitors participated in to anticipate their responses. Overall, results indicated that managers at this particular park were accurate in anticipating visitor responses to certain experiential factors and visitor preferences towards certain management actions and park services. Results from this study have important implications not only for how VUM researchers understand assumptions in the discipline but also how PPA managers approach their decision-making process, particularly those decisions that impact the visitor experience. To address the third research question, semi-structured interviews were conducted to identify major themes and learning outcomes retained by students in recreation-related majors. Continuing to build on the first chapter, this study investigated whether identified assumptions were being perpetuated in courses that discussed aspects of VUM. This understanding has important implications for how relevant subject material is disseminated in the classroom as well as for how future PPA managers achieve their mission. While results indicated that assumptions presented in previous research were not being overly perpetuated in the classroom, findings do suggest that there are some potential gaps to be filled and addressed in how recreation-related majors are structured. This study sheds light on how students in this field are being prepared for work as potential PPA managers, as well as how faculty and instructors of such courses approach the subject matter. Ultimately, this dissertation offers insight into, and recommendations for, ensuring best practices are being followed and promoted within the VUM field.
Keywords: Visitor use management; Parks and protected areas; Research assumptions; Park management